(untitled) (Social and Environmental Law Journal, 2024)
This article will talk about the actions of the Inter-American Commission of Human Rights (IACHR) on behalf of women who are victims of violence resulting from the activities of paramilitarism and guerrillas and those who could not find reparation for their rights or support on the State. Through the historical analysis and reports presented to the IACHR, we can observe the extent of female invisibility within Colombian territory and how they become true “instruments of war” in the hands of these organizations.